Small molecules targeting Mcl-1: the search for a silver bullet in cancer therapy. Issue 5 (5th April 2016) - Nhu, Duong; Lessene, Guillaume; Huang, David C. S.; Burns, Christopher J.
Abstract : Progress towards the development of potent and selective inhibitors of the pro-survival protein Mcl-1 is reviewed. Abstract : Mcl-1 (myeloid-cell-leukemia-sequence-1) is a pro-survival member of the Bcl-2 family of proteins. Mcl-1 has been shown to be critical to the survival of a variety of cancer cells and to mediate resistance to conventional and targeted chemotherapeutics. Whilst potent and selective small molecule inhibitors of Bcl-2 and Bcl-XL have been developed, the discovery of selective inhibitors of Mcl-1 has proven more problematic and only very recently have potent and selective inhibitors been described. In this review we outline key features of Mcl-1 biology, and chemical approaches and outcomes of inhibiting this important survival protein for the treatment of cancers.